Analysis of talent management aspects : Drive towards Alignment of Talent Management and Business Strategy - Dr.Swati N. Rahate (International Journal of Advanced Science and Technology, 2020)
HR skills are the coaches whereas talent management strategy and Business strategy are the books they use to make decisions. The talent management strategy outlines how the interconnected programs work together to keep people engaged and productive. Progressive organizations always looking for the ways to align their business strategy with how they manage people. Comprehensive talent management strategies can include programs for recruiting, training and development, performance management, leadership development, succession planning and more. The practices in these programs put the primary focus on meeting people’s needs and the interlocking nature creates a strategic foundation that leads to better business results. With a comprehensive talent strategy that’s aligned to the business strategy, results in effective implementation of the talent management programs to bring in the right people at the right time. It also becomes effective to ensure people stay engaged in their work so they don’t leave. In today’s ever-changing workplace, organizations need to make it a priority to meet the needs of the people that keep their business going strong. The study is carried out in IT sectors of Maharashtra which are in regular practice of conduction of talent management programs.Data has been collected through the process of interviewing higher authorities and employees of the organizations and by conducting questionnaire survey for employees. Samples of employees for survey are selected randomly, whereas samples of higher authorities for interview are selected according to convenience. Collected data has been systematically pooled for further analysis. Hypothesis testing has been done with the help of ANNOVA test, Regression analysis and CART Analysis (Classification and Regression Tree analysis)